Caracterização funcional e bioquímica do fator de transcrição HsfA e estudo da termotolerância, composição lipídica e integridade da parede celular de Aspergillus fumigatus - Fabri, João Henrique Tadini Marilhano (Universidade Federal de São Carlos, 2022)
The filamentous and saprophytic fungus Aspergillus fumigatus is the main causative pathogen of invasive pulmonary aspergillosis (API) in immunocompromised individuals. One of its most important determinants of virulence is the thermotolerance. Faced with high temperature stress, opportunistic fungal pathogens implement an adaptive mechanism known as heat shock response controlled by heat shock transcription factors (HSFs), such as Hsf1. In eukaryotes, HSFs regulate the expression of heat shock proteins, such as the chaperone Hsp90, which are part of the cellular program for heat adaptation. Recently, it was observed that the disturbance in cell wall integrity (CWI) of A. fumigatus also causes susceptibility to elevated temperatures. Furthermore, it is known that, in response to temperature shock, fungi adapt the composition and fluidity of their cell membranes towards homeostasis. In this work, the hsfAHSF1 gene from A. fumigatus was studied, through the construction of a conditional mutant. hsfA was essential for the viability, virulence, thermotolerance and CWI of A. fumigatus. Temperature shock and cell wall stress modified the cell wall ultrastructure and triggered the coordinated expression of HsfA and Hsp90, which was shown to be regulated by the components of the CWI pathway PkcA and MpkA. RNA-Seq analyzes confirmed that HsfA regulates the expression of genes related to heat shock response, cell wall biosynthesis and remodeling, and lipid homeostasis. Furthermore, HsfA had a role in the synthesis of sphingolipids and phospholipids. For this reason, the function of the sdeAOLE1 gene, which encodes a fatty acid desaturase, and its relationship with hsfA was also investigated here. sdeA was shown to be essential, necessary for the synthesis of fatty acids and important for the phospholipids metabolism. It was also observed that HsfA regulates the expression of sdeA and the pseudogene sdeB. Finally, Western blot analysis proved that SdeA physically interacts with Hsp90 and regulates the expression of this chaperone. Collectively, these results demonstrate the connections between heat shock response and the CWI pathway and plasma membrane homeostasis, with HsfA playing a crucial role in the regulation of these pathways. Such conclusions may be important to bring new information about potential therapeutic targets in the treatment of API, and can also be applied to other pathogenic or relevant filamentous fungi.
Functional characterization of HsfA transcription factor and study of the thermotolerance, lipid composition and cell wall integrity in Aspergillus fumigatus
Keywords: Aspergillus fumigatus; Termotolerância; Choque térmico; HsfA; Parede celular; Fosfolipídios; SdeA; CIENCIAS BIOLOGICAS::GENETICA